Individual psychotherapy in alcohol dependence - Kalyoncu, Ayhan; Mırsal, Hasan (Journal of Dependence, 2002)
Psychodynamic oriented psychotherapies are one of the treatment modalities that have not had an important part in current treatment programs of alcohol dependence. In the psychodynamic therapies alcohol use is considered to be a symptom of unconscious conflicts. Early psychodynamic explanations define addiction as a conclusion of arrested psychosexual development. Afterwards environmental social factors are considered to be an important contributor to the development of personality and to the problematic behaviour which might be also related to conflicts in social roles. In this article, the psychodynamic oriented individual psychotherapy is reviewed in the treatment of alcohol dependence. Besides, an eclectic-integrative individual psychotherapy model for alcohol dependence has been submitted.
Keywords: Alcohol dependence; individual psychotherapy; psychodynamic psychotherapy